DIGITALISASI SISTEM PENJUALAN MENGGUNAKAN APLIKASI ACCURATE PADA PT XYZ - Leilanirma Gantari Ariyafan; Siti Sundari (PT. Media Edutama Nusantara, 2026)
The advancement of information technology has prompted companies to digitalize their sales systems in order to enhance transaction efficiency, accuracy, and the reliability of financial information. PT XYZ, a medical equipment manufacturing company with a high volume of transactions and credit facilities, requires an integrated system for managing receivables and controlling cash flow. This study employs a qualitative descriptive method, collecting data through observation and analysis of the company’s internal documents. The research focuses on the implementation of the Accurate software in recording sales transactions, managing inventory and receivables, as well as comparing the efficiency between manual and automated systems. The results indicate that Accurate improves processing time efficiency and ensures greater data accuracy. The system facilitates the generation of receivables reports, invoices, and reconciliations while enhancing transparency and internal control. In conclusion, the digitalization of the sales system through Accurate significantly accelerates sales processes, minimizes input errors, improves the reliability of financial reporting, and supports more effective managerial decision-making.